Let's speak for Patient Safety in India - Kansal, Om Prakash (Indian Journal of Community Health, 2017)
As if the fire episode in a major hospital in 2011 in Kolkata was not enough, another fire episode was recorded in West Bengal tertiary hospital end August. Recently, a colleague undertaking infection control audit was led into an operating theatre with blood stained slippers and only face mask, when the surgery was on. The onset of hepatitis B and hepatitis C epidemics due to reuse of syringes and needles hit the regional headlines in Haryana and Srinagar in 2012 and 2015 respectively. Worldwide, adverse events occur in around 10% of hospital patients. Individual studies have reported adverse events from 4–17% of hospital admissions and 5–21% of these adverse events result in death. In low- and middle-income countries, adverse events may develop from unsafe care in as many as 18.4% of patients, with 30% of those events leading to the patient's death. Medical literature often reports the incidence of health care acquired infections which the patient may not have when s/he walks in the hospital. The evidence also suggests that half of these can be prevented easily just by investing a minor fraction of the budgets while planning the healthcare. In India, almost all states are facing this challenge irrespective how robust the health care delivery system has developed.